EFFECTIVENESS OF REPRODUCTIVE AND SEXUAL HEALTH PROGRAMS FOR PROSPECTIVE BRIDGES (CATIN) IN IMPROVING CATIN'S KNOWLEDGE AND ATTITUDES OF CATIN IN GUNUNGSARI PUBLIC HEALTH CENTER IN 2018 (Effectivity of Premarital Counseling on Health Reproduction Knowle - Kusniyati Utami; Agus Supinganto; Irni Setyawati; Irwan Budiana (Dinasti Publisher, 2021)
Reproductive and sexual health program for prospective brides is one of programs implemented by government where these activities are aimed at women from adolescence before pregnancy prepare women to become healthy pregnant women and ensure health of mothers so that they can give birth to a healthy and quality generation. Purpose: This study aims to determine effectiveness of the implementation of IEC program on sexual and reproductive health of bride and groom at Gunungsari Public Health Center in 2018. Methods: This study was conducted with a cross-sectional design with a case-control approach, sampling technique used was proportional random sampling. Data collection was carried out on 38 primigravida pregnant women who visited the public health center with a history of participating in IEC catin program as observation group and 38 respondents from primigravida mothers with a history of not participating in KIE catin program as control group. Then data were analyzed by using chi-square. Results: Results showed that knowledge of sexual and reproductive health in two groups did not have a difference (p = 1,000), as did catin's attitudes towards sexual and reproductive health in two groups (p = 0.487). IEC and sexual health are less effective in increasing knowledge and attitudes. Discussion: The need for more specific program evaluation to increase outcomes by program objectives. Multiple workflows, standard procedures, and program performance should be reviewed by program objectives to increase success. Also, cooperation with several related parties is necessary as an effort to increase public awareness to actively participate in program.